Women's Satisfaction of Maternity Care in Nepal and Its Correlation with Intended Future Utilization. (8th November 2015) - Paudel, Yuba Raj; Mehata, Suresh; Paudel, Deepak; Dariang, Maureen; Aryal, Krishna Kumar; Poudel, Pradeep; King, Stuart; Barnett, Sarah
Abstract : The impact of rapid increase in institutional birth rate in Nepal on women's satisfaction and planned future utilization of services is less well known. This study aimed to measure women's satisfaction with maternity care and its correlation with intended future utilisation. Data came from a nationally representative facility-based survey conducted across 13 districts in Nepal and included client exit interviews with 447 women who had either recently delivered or had experienced complications. An eight-item quality of care instrument was used to measure client satisfaction. Multivariate probit model was used to assess the attribution of different elements of client satisfaction with intended future utilization of services. Respondents were most likely to suggest maintaining clean/hygienic health facilities (42%), increased bed provision (26%), free services (24%), more helpful behaviour by health workers (18%), and better privacy (9%). Satisfaction with the information received showed a strong correlation with the politeness of staff, involvement in decision making, and overall satisfaction with the care received. Satisfaction with waiting time ( p = 0.035), information received ( p = 0.02), and overall care in the maternity care (<0.001) showed strong associations with willingness to return to facility. The findings suggest improving physical environment and interpersonal communication skills of service providers and reducing waiting time for improving client satisfaction and intention to return to the health facility.